An experimental study on angled trash screen in open channels - Mahmoud Zayed; Anas El Molla; Mohammed Sallah (Alexandria Engineering Journal, 2018)
Trash screens are widely employed at entrance of hydraulic structures (culverts, barrages…, etc.), water intakes, and pumping stations to trap flowing debris that could instigate downstream troubles. Traditional trash screen (perpendicular-vertical screen to the flow direction) can cause problems of increasing head loss through it, especially with the blockage ratio. This experimental study presents a concept of an adjusted screen with circular bars to find a solution for such problem. In this regard, angled screen models with different angles, blockage ratios, and flow discharges were investigated. The results indicated that the head loss coefficients reduced by reducing the screen angle, so angled screen (α < 90°) reduced the loss in comparison with the traditional trash screen (α = 90°). The values of head loss coefficient increased with increasing blockage ratio, and flow discharge. The screen losses increase strongly when the screen becomes blocked by 40% or more. Screen angle, blockage ratio, and discharge influence effectively the head loss of a screen. Furthermore, a new equation for the head loss, the key element in designing screens, is proposed based on the different tested parameters, and should be useful in designing trash screens. Keywords: Angled trash screen, Experimental hydraulics, Open channel flow, Head loss